Detrital zircon similarities and dissimilarities between the Iberian Pyrite Belt, Ossa-Morena Zone and Meguma - João Lains Amaral; Ana Rita Solà; Telmo Bento dos Santos; Martim Chichorro (Geologica Acta, 2023)
Despite the so-called exotic nature of the South Portuguese Zone relatively to the other major domains of the Iberian Massif of peri-Gondwanan affinity, Devonian detrital rocks of the oldest strata in the Iberian Pyrite Belt have a remarkable resemblance with the Ossa-Morena Zone’s Neoproterozoic-Cambrian rocks and the West Meguma’s Cambrian-Ordovician rocks, presenting the so-called “West African signature”. Using published U-Pb detrital zircon data, we discuss the similarities and dissimilarities between the Iberian Pyrite Belt, Ossa-Morena Zone and West Meguma Terrane through multidimensional scaling, comparing them with other zones of the Iberian Massif, Saxo-Thuringian Zone, Avalonia-Ganderia, and the North African cratonic regions. Our findings show that multidimensional scaling is not entirely effective in displaying the dissimilarities between the peri-Gondwanan terranes due to the background noise caused by the overwhelming number of Cadomian-Panafrican ages. However, it becomes a powerful tool if these ages are filtered. A dominant Meguma-type provenance (Cambro-Ordovician) for the Middle-Upper Devonian rocks of the Iberian Pyrite Belt is demonstrated, mainly attending to their similar Birimian-Eburnean pattern. The possibility of minor contributions from the lower Cambrian rocks of the Ossa-Morena Zone into the Iberian Pyrite Belt quartzites is unlikely, as the latter lack the 1.9Ga peak that characterises the Ossa-Morena Zone sediments. Additionally, the remarkable similarities between Ossa-Morena Zone’s and West Meguma’s detrital rocks strongly suggest a similar paleogeographic setting (but diachronic) for both terrains from the Ediacaran to Lower Ordovician times relative to the North African blocks.